Hubungan Asupan Natrium, Vitamin C, Rasio Lemak Omega 3 dan Omega 6 dengan Kejadian Penyakit Jantung Koroner di RSUD Al Ihsan Jawa Barat - Irawan, Galuh Chandra; Ratna; Yuliati (Universitas Muhadi Setiabudi, 2024)
Coronary heart disease (CHD) is one causes of death in Indonesia. one of risk factor can be modified coronary heart disease are sodium intake, vitamin C intake, the ratio of PUFA fat intake. The purpose of this study was to determine the relationship between intake of sodium, vitamin C, the ratio of omega 3 and omega 6 fats with the incidence of coronary heart disease (CHD). This study was an observational with a case control design from 46 sample. This study uses the Chi Square test and Odds Ratio to see the risk. To see the statistical significance of the relationship using the level of confidence (95% CI) and p <α (0.05). Statistical test results showed that high sodium intake had a significant relationship with p<α (0.001), vitamin C intake did not have a significant relationship with p<α (0.7), the ratio of omega 3 and omega 6 fat intake has a significant with p<α (0.000). Conclusion : there is a relationship between sodium intake, ratio of omega 3 and omega 6 fat with coronary heart disease (CHD), but there is no relationship with vitamin C intake in Al Ihsan Hospital.